Acoustic settings combination as a sensory crispness indicator of dry crispy food - Dias-Faceto, Liara S.; Salvador, Ana; Conti-Silva, Ana C. [UNESP] (Wiley, 2020)
Crispness is a critical attribute of quality for crispy products, which can be evaluated through both instrumental and sensory analyses. The aim of the study was to identify the best combination of settings of a device coupled to a texture analyzer for acoustic analysis in order to find strong correlations with the sensory texture. For that, nine commercial food products were submitted to force and acoustic (acoustic envelope detector) analyses, using two settings for acoustic data acquisition (gain 1 and gain 4), and two settings for acoustic data management (threshold 0.5 and 2.5). The products were also evaluated using texture descriptive sensory analysis. The gain changing from 1 to 4 (enhancing the test sensitivity) increased the number of acoustic peaks and reduced the sound pressure level. Changing the threshold from 0.5 to 2.5 (reducing the interference of background noise on the acquired data) reduced the number of acoustic peaks. The correlation between the instrumental and the sensory analysis showed gain 1 as the most adequate acoustic setting to obtain the acoustic parameters of products with different crispness intensities. Moreover, threshold 2.5 is the most appropriate for acoustic data collection. Therefore, sensory attributes and instrumental properties strong correlations indicate that texture analyzer in combination with the acoustic envelope detector is a good instrument to mimic human mastication and texture perception, through both force and sound stimuli. This study about dry crisp food may contribute to the literature and food industry, as well to future studies about wet crispy and crunchy foods.
Keywords: acoustic envelope detector (AED); correlation; instrumental force; sound emission; texture analyzer